Time to Delivery after Scheduled Shirodkar Cerclage Removal in Singleton Gestations based on the Original Indication for Cerclage Placement - Bigelow, Catherine A.; Fox, Nathan S.; Lam-Rachlin, Jennifer; Gupta, Simi; Naqvi, Mariam; Romero, Julie; Rebarber, Andrei (American Journal of Perinatology, 2019)
Objective To estimate the time to delivery after elective cerclage removal and evaluate whether there is a difference based on the indication for cerclage placement.Study Design This was a retrospective cohort of singleton pregnancies that underwent Shirodkar cerclage placement at a single maternal–fetal medicine practice between June 2005 and June 2017. We included all scheduled elective cerclage removals >36 weeks. The primary outcome was latency to delivery. We further compared time to delivery based on the original indication for cerclage. Data were analyzed using the one-way analysis of variance and chi-square test.Results A total of 143 patients met the inclusion criteria. Of these, 40.6% were history indicated, 51.0% ultrasound indicated, and 8.4% exam indicated. The mean time from removal to delivery was 13.3 ± 8.4 days; 12.6% (18/136) of patients delivered within 24 hours of removal. When stratified by indication for cerclage, there were no significant differences for all delivery outcomes. Delaying cerclage removal to >37 weeks resulted in a statistically significantly later gestational age at delivery compared with removal between 36 and 366/7 weeks (39.0 vs. 38.3 weeks, p = 0.001).Conclusion The mean time from elective Shirodkar cerclage removal to delivery is 13 days with only 12.6% of patients delivering within 24 hours of removal.
Keywords: cerclage removal; latency to delivery; preterm birth; Shirodkar cerclage